Analisis Pengendalian Kualitas Menggunakan Metode Six Sigma : (Studi Kasus PT Andalan Mandiri Busana ) - Apriliana Nur Choirun Nisa; Rayhan Gunaningrat; Indra Hastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Quality control is crucial for the company to minimize the existence of defective products. The research focuses on the quality control section. The purpose of this study is to find out how the implementation of quality control occurs at PT Andalan Mandiri Busana, identify the factors that cause defects in garment products, and determine proposed improvements as an effort to suppress defective products. The results showed that there were factors that caused production defects and the biggest cause was broken stitches, and the sigma value obtained was 4.15, which means that the company has carried out pretty good quality control. Based on this research, the recommendations that can be given are in the improve stage, in the form of a table of proposed improvements using the Five M-checklist approach and Kaizen based on fishbone diagrams. The results of this study are expected to be one of the inputs for companies in implementing quality control and can increase the company's sigma level.